La literatura infantil ecuatoriana en el desarrollo del lenguaje en los niños de nivel inicial II, en la Unidad Educativa Cristiana Nazareno de la ciudad de Riobamba, periodo 2020 – 2021 - Ortiz Lucero, Angela Vanessa (2021)
The present research entitled "Ecuadorian infantile literature in the development of language in children of initial level II, at the Nazareno Christian educational unit of the city of Riobamba, during 2020-2021", aimed to analyze the role of literature at the initial level, and to identify the favorable aspects and the existing relationship between the infantile literature and education. To that end, we carried out a bibliographic investigation for the two identified variables; the independent as Ecuadorian Infantile Literature, and the dependent as the development of language in children of the initial level II. The research methodology has a qualitative, non-experimental approach. Because of the level and design, it is considered as a bibliographic, and field research. We have obtained favorable results regarding the teachers' assessment of the application of literature at the initial level. In this regard, the students have collaborated allowing us to assess from our perspective that there are aspects related to Ecuadorian infantile literature and its importance in language development.